Morphometric Characteristics and Body Indices as Selection Criteria for Female Bali Cattle in East Kalimantan - Rahmi, Siti Aulia; Wahjuningsih, Sri; Nurgiartiningsih, Veronica Margareta Ani (Faculty of Animal Science, Universitas Brawijaya, 2025)
Bali cattle constitute one of Indonesia's native germplasm sources for meat supply. Beef is one of the primary sources of protein that plays a crucial role in meeting the nutritional needs of the community. The research material consisted of 251 female Bali cattle aged 12 months and 24 months. These Bali cattle belong to the farmer group in Bontang city, Kutai Timur Regency (Kutim), Berau Regency, Kutai Kartanegara Regency (Kukar), Penajam Paser Utara Regency (PPU), and Paser Regency. The morphometric traits measured were withers height (WH), chest girth (CG), and body length (BL). The data obtained were analysed via analyses of variance, and if there were significant differences, the analysis was continued until a least significant difference was detected. The results revealed significant differences in the morphometric characteristics of 12-month-old Bali cattle across regions (P<0.01). The highest WH was from Bontang cattle (104.30±3.16a), and the lowest was from PPU (98.94±6.79c). The CG of Bontang cattle also had the highest value (131.30±6.29a), and the lowest value was from PPU (119.59±7.34b), with the highest BL of cattle from Berau (101.22±2.73a) and the lowest value from PPU (93.35±4.89b). Twenty-four-month-old female Bali cattle also presented significant morphometric differences (P<0.01) across regions. Cattle from the PPU consistently excelled in all parameters: WH (108.00±2.24a), CG (138.40±3.51), and BL (110.60±6.66a). The lowest WH was cattle from Berau at WH (101.33±0.58b), CG (126.00±2.65), and BL (97.33±4.62b). In conclusion, on the basis of observations of withers height, heart girth, and body length, all individual samples met the Indonesian National Standard (SNI) criteria for female Bali cattle breeding stock. Significant morphometric differences are caused by local genetic selection factors, the environment, feed availability, feed quality, and management practices.